The role of nutrition in analysis of risk factors and short-term outcomes for late-onset necrotizing enterocolitis among very preterm infants: a nationwide, multicenter study in China - Kun-Yao Hong; Yao Zhu; Fan Wu; Jian Mao; Ling Liu; Rong Zhang; Yan-Mei Chang; Wei Shen; Li-Xia Tang; Xiu-Zhen Ye; Yin-Ping Qiu; Li Ma; et al. (BMC, 2024)
Abstract Background Necrotizing enterocolitis (NEC) is a serious gastrointestinal disease, primarily affects preterm newborns and occurs after 7 days of life (late-onset NEC, LO-NEC). Unfortunately, over the past several decades, not much progress has been made in its treatment or prevention. This study aimed to analyze the risk factors for LO-NEC, and the impact of LO-NEC on short-term outcomes in very preterm infants (VPIs) with a focus on nutrition and different onset times. Method Clinical data of VPIs were retrospectively collected from 28 hospitals in seven different regions of China from September 2019 to December 2020. A total of 2509 enrolled VPIs were divided into 2 groups: the LO-NEC group and non-LO-NEC group. The LO-NEC group was divided into 2 subgroups based on the onset time: LO-NEC occurring between 8 ~ 14d group and LO-NEC occurring after 14d group. Clinical characteristics, nutritional status, and the short-term clinical outcomes were analyzed and compared among these groups. Results Compared with the non-LO-NEC group, the LO-NEC group had a higher proportion of anemia, blood transfusion, and invasive mechanical ventilation (IMV) treatments before NEC; the LO-NEC group infants had a longer fasting time, required longer duration to achieve the target total caloric intake (110 kcal/kg) and regain birthweight, and showed slower weight growth velocity; the cumulative dose of the medium-chain and long-chain triglyceride (MCT/LCT) emulsion intake in the first week after birth was higher and breastfeeding rate was lower. Additionally, similar results including a higher proportion of IMV, lower breastfeeding rate, more MCT/LCT emulsion intake, slower growth velocity were also found in the LO-NEC group occurring between 8 ~ 14d when compared to the LO-NEC group occurring after 14 d (all (P < 0.05). After adjustment for the confounding factors, high proportion of breastfeeding were identified as protective factors and long fasting time before NEC were identified as risk factors for LO-NEC; early feeding were identified as protective factors and low gestational age, grade III ~ IV neonatal respiratory distress syndrome (NRDS), high accumulation of the MCT/LCT emulsion in the first week were identified as risk factors for LO-NEC occurring between 8 ~ 14d. Logistic regression analysis showed that LO-NEC was a risk factor for late-onset sepsis, parenteral nutrition-associated cholestasis, metabolic bone disease of prematurity, and extrauterine growth retardation. Conclusion Actively preventing premature birth, standardizing the treatment of grade III ~ IV NRDS, and optimizing enteral and parenteral nutrition strategies may help reduce the risk of LO-NEC, especially those occurring between 8 ~ 14d, which may further ameliorate the short-term clinical outcome of VPIs. Trial registration ChiCTR1900023418 (26/05/2019).